Brassica juncea Peroksidase Sebagai Biokatalis Dalam Sintesis Kopling Oksidatif Senyawa Guaiakol - YULIA ANITA; HANI MULYANI (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Isolation of phenolic polymers from plants are challenging because the low yield and time consuming. Synthesis of phenolic polymer is urgently needed to overcome the lack of the compounds. Phenolic oxidation with H2O2 by peroxidase, results oxidative coupling reaction and finally produces phenolic polymers. Peroxidase (e.g guaiacol) catalyzes oxidative reaction by hydrogen peroxide with substrate acted as hydrogen donor. In this study, peroxidase from sawi hijau (Brassica juncea) was isolated. The obtained crude peroxidase had specific activity 5.618U/mg protein. Reaction between guiacol, H2O2 and crude peroxsidase produced guaiacol dimer. The new dimer was identified by NMR spectrometry, and the product showed coupling in para-para of 4,4’-biguaiakol, with 17% yield. In summary, crude peroxidase obtained from sawi hijau (Brassica juncea) was able to act as a catalyst for the oxidative coupling reaction of guiacol into guaicol dimer compounds.